Electroacupuncture alleviates orofacial allodynia and anxiety-like behaviors by regulating synaptic plasticity of the CA1 hippocampal region in a mouse model of trigeminal neuralgia - Jia, Yu-Zhi; Li, Hai-Tao; Zhang, Guang-Ming; Wu, Hong-Yun; Zhang, Si-Shuo; Zhi, Hong-Wei; Wang, Ya-Han; Zhu, Jing-Wen; Wang, Yi-Fan; Xu, Xiang-Qing; Tian, Cai-Jun; Cui, Wen-Qiang (Frontiers in Molecular Neuroscience, 2022)
Objective Trigeminal neuralgia (TN), one of the most severe and debilitating chronic pain conditions, is often accompanied by mood disorders, such as anxiety and depression. Electroacupuncture (EA) is a characteristic therapy of Traditional Chinese Medicine with analgesic and anxiolytic effects. This study aimed to investigate whether EA ameliorates abnormal TN orofacial pain and anxiety-like behavior by altering synaptic plasticity in the hippocampus CA1. Materials and methods A mouse infraorbital nerve transection model (pT-ION) of neuropathic pain was established, and EA or sham EA was used to treat ipsilateral acupuncture points (GV20-Baihui and ST7-Xiaguan). Golgi–Cox staining and transmission electron microscopy (TEM) were administrated to observe the changes of synaptic plasticity in the hippocampus CA1. Results Stable and persistent orofacial allodynia and anxiety-like behaviors induced by pT-ION were related to changes in hippocampal synaptic plasticity. Golgi stainings showed a decrease in the density of dendritic spines, especially mushroom-type dendritic spines, in hippocampal CA1 neurons of pT-ION mice. TEM results showed that the density of synapses, membrane thickness of the postsynaptic density, and length of the synaptic active zone were decreased, whereas the width of the synaptic cleft was increased in pT-ION mice. EA attenuated pT-ION-induced orofacial allodynia and anxiety-like behaviors and effectively reversed the abnormal changes in dendritic spines and synapse of the hippocampal CA1 region. Conclusion EA modulates synaptic plasticity of hippocampal CA1 neurons, thereby reducing abnormal orofacial pain and anxiety-like behavior. This provides evidence for a TN treatment strategy.